Prevalence of polypharmacy in octogenarians attended at an outpatient clinic in the interior of Espírito Santo - Dias de Castro Luz, Ana Alice; Pezzin, Josiane; Pessoa Hemerly, Jefferson (JORNAL DE ASSISTÊNCIA FARMACÊUTICA E FARMACOECONOMIA, 2025)
Objective: To evaluate the prevalence of polypharmacy and drug-related problems (DRP) in octogenarians treated at a SUS outpatient clinic in the interior of Espírito Santo. Methods: Exploratory, descriptive study with a qualitative-quantitative approach. The study included elderly people (IP) aged 80 years or over treated at the SUS specialty outpatient clinic located in the interior of the Espírito Santo. After the geriatric medical consultation, the patient was referred to pharmaceutical care, where sociodemographic information, health history and medication use were collected. Results: 41 octogenarians were treated, whose average age was 86 years, with the majority being women (61%) with chronic disease such as hypertension (82,9%), dyslipidemia (56,1%), diabetes (41, 46%) and pain (63,4%). The average number of medications used by octogenarians was 7,6, with antihypertensives, antidepressants and analgesics being common. Although 68.3% reported knowing their treatments, 53.7% had DRP, with non-adherence (32%) being the most prevalent condition. Conclusion: The data show that the octogenarians treated have low education and many chronic diseases. With regard to the use of medications, polypharmacy is accompanied by DRP, especially non-adherence. Therefore, it is necessary to expand strategies to promote health care suited to the needs and understanding of octogenarians. The pharmacist must develop practices aimed at this group to promote the rational use of medicines, contributing to the quality of life of octogenarians.